Élaboration d’une terminologie juridique en hausa dans le roman « Le Nouveau Juge » d’Amadou Ousmane - BAARE, Sani (Language Policy in Africa, 2026)
This study focuses on the development of a Hausa legal terminology based on Amadou Ousmane’s literary work Le Nouveau Juge, entitled Sabon Alƙali in Hausa. The research involves the preselection of French legal terms and the identification of their equivalents in Hausa, with the aim of establishing a specialized lexical resource. These terms are particularly relevant for media professionals, researchers, and individuals interested in the legal field. Hausa, a national language widely spoken in Niger, is also a transnational lingua franca used in northern Nigeria and across several West African countries. As a member of the Chadic branch of the Afro-Asiatic family, Hausa plays a central role in regional communication. Translating the legal concepts found in the novel not only facilitates comprehension of its literary message but also enriches Hausa with essential juridical vocabulary, while safeguarding the integrity of the original concepts. The objective of this work is to elaborate a specific legal terminology that makes the text accessible to Hausa speakers and ensures consistency with both French and Hausa legal systems. The methodology consists of selecting legal terms from the novel and examining their translations, while seeking appropriate anchoring in the two linguistic and institutional contexts.The results of this research will serve as a terminological database, providing a reference tool for anyone wishing to express themselves in Hausa within the legal domain. Ultimately, this contribution promotes the valorization of Hausa in professional and academic practices, while fostering linguistic equity and accessibility in the field of law.